2021
DOI: 10.3389/fneur.2021.633320
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Neurophysiological Effects of Repeated Head Trauma in Retired Australian Male Sport Athletes

Abstract: Aim: This study investigated the somatosensory and corticomotor physiology of retired contact sport athletes with a history of repeated concussion/subconcussion head trauma.Methods: Retired male athletes with a history of playing contact sports and repeated head trauma (n = 122) were divided into two groups: those who expressed concerns regarding their mental and cognitive health (“symptomatic”: n = 83), and those who did not express any ongoing concerns (“asymptomatic”: n = 39). Both groups were compared to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…Studies have shown neurobehavioral, pathophysiological and pathological alterations after a single traumatic insult; but despite some variability in results in repeat insult models reflecting methodological differences, the overall data demonstrates far worse longitudinal outcomes following rTBI and mmTBI. Through Hill's criterion of experiment, the findings from pre-clinical RHI studies replicating elements of observed human pathophysiological (140,141), imaging (142,143), and epidemiological studies (21) suggests a causal relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown neurobehavioral, pathophysiological and pathological alterations after a single traumatic insult; but despite some variability in results in repeat insult models reflecting methodological differences, the overall data demonstrates far worse longitudinal outcomes following rTBI and mmTBI. Through Hill's criterion of experiment, the findings from pre-clinical RHI studies replicating elements of observed human pathophysiological (140,141), imaging (142,143), and epidemiological studies (21) suggests a causal relationship.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously employed the fatigue and related symptom survey to characterise and quantify our cohorts, particularly those who express ongoing self-reported symptoms compared to those who report no ongoing symptoms (Pearce et al, 2020; Pearce et al, 2021). We found significant differences between the groups we studied, with the self-concern group having the highest scores.…”
Section: Discussionmentioning
confidence: 99%
“…Employing previously published methods in similar cohorts (Pearce et al, 2014; Pearce et al, 2021; Pearce et al, 2018), corticospinal excitability was quantified via single-pulse TMS, delivered over the contralateral primary motor cortex. Surface electromyography (sEMG) measured motor evoked potentials (MEPs) recording 500 ms sweeps (100 ms pre-trigger, 400 ms post-trigger; PowerLab 4/35, ADInstruments, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations